A salt lick to fertilize soils - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
'Kanwa' is a mineral salt that is extracted from the subsoil in northeastern Nigeria. It is transported to the sub-humid zone of the country where it is sold to Peuhl Pastoralists who use it to supplement their cattle feed. According to a recent...